Assessment of knowledge and practices of biomedical waste management and infection control among health assistants in a rural block of Nadia district, West Bengal - Pal, Jayita; Biswas, Mrinal; Nandi, Swagata; Biswas, Asit Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Improper biomedical waste management, inadequate precautions to prevent needle stick injuries and air-borne infections among health care workers can lead to several hazards not only to them, but community can also be in danger due to environmental pollutions or risk of transmission of diseases. Sub-centres are the peripheral most points to deliver health services and health assistants posted there are in a unique position to get infected frequently if they are not adhering to standard protocols to manage these problems. The current study aimed to assess the status of infrastructure of sub-centres, knowledge and practices of the health assistants related to biomedical waste management and infection control. Methods: A cross-sectional study had been conducted in 40 sub-centres of Chakdaha block, Kalyani subdivision, Nadia district, West Bengal, selected purposively. All the health assistants were interviewed after taking informed consent with a pretested predesigned semi-structured questionnaire. An observational checklist had been used to assess infrastructure of the sub-centres and also some practices of the health assistants. Results: More than half of the study population (61.6% and 63%) secured poor score regarding knowledge and practices related to biomedical waste management and infection control respectively. There was no relationship between knowledge and practices of the same (p=0.187). Conclusions: Pre-service and also frequent in-service training should be conducted to improve the knowledge and practices of the health assistants. Regular monitoring, supervision of their day to day work by the higher authority, can improve their attitude and practices related to such an important public health issue.